Infrastructure indices: Comparative analysis of performance, risk and representation of global listed proxies - Dimitar Lambrev (Naše gospodarstvo / Our Economy, 2019)
Faced with historically low interest rates, investors are looking further into illiquid assets such as infrastructure in search of alternative sources of income, better diversification and a long-term investment perspective. This paper analyzes the key performance and risk characteristics of the EDHECinfra global unlisted infrastructure equity index when compared to the main global listed infrastructure indices during the 2001-2018 period. The descriptive statistics method is applied to determine the representation of the benchmarks commonly used by investors considering infrastructure investments. For the purpose of the market beta analysis, the MSCI World index is also used as a global equities proxy in a linear regression model. Listed infrastructure is often considered as an income-yielding and defensive equity strategy that provides a liquid proxy for alternative assets (e.g., infrastructure). However, the paper results indicate that the net effect of investing in listed infrastructure remains questionable, even unknown. Recent empirical findings demonstrate divergent stands on benchmarking infrastructure. The high correlation of the main listed infrastructure indices with the broad equity index MSCI World and the inconsistency of research results thus far suggest that infrastructure is an ill-defined investment category within the listed infrastructure space with lacking reliable and useful benchmarking. The commonly used and far-reaching classification of companies with broad industrial nature and business activities that are less relevant to infrastructure may affect the overall representation of the legitimate characteristics of the infrastructure asset class amid the growing enthusiasm among investors.
Keywords: G10; G11; G15; G23; H54; 330; infrastructure; index; benchmarking; listed equity; performance analysis